Learning Trajectory in Mathematical Proof. Issue 1 (February 2021) - Minggi, I; Mulabar, U; Assagaf, S F
Abstract: This study aims to obtain a learning trajectory framework for mathematical proofing and to develop teaching materials for the real number system topic. The method is Design research. The results showed the five developed trajectories: (a) experience and fundamentals, (b) simple proof (c) proof of existence, (d) complex proof. and (e) proofing through construction. In proofing, the students still need scaffolding from the lecturer. The difficulties was still existed are writing symbols and writing mathematical reasoning especially in linking a series of statements in the proof..